2016
DOI: 10.1097/hcm.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hospital Market Competition on Patient Mortality and Total Performance Score

Abstract: The Affordable Care Act of 2010 launch of Medicare Value-Based Purchasing has become the platform for payment reform. It is a mechanism by which buyers of health care services hold providers accountable for high-quality and cost-effective care. The objective of the study was to examine the relationship between quality of hospital care and hospital competition using the quality-quantity behavioral model of hospital behavior. The quality-quantity behavioral model of hospital behavior was used as the conceptual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Based on the work of Berwick and others, in 2013, the Centers for Medicare and Medicaid Services (CMS) initiated the hospital Value-Based Purchasing (VBP) program that altered hospital reimbursement from procedure-based to hospital performance data. This novel approach has challenged medical institutions to deliver high-quality care and reduce costs (Haley et al, 2016). As of 2018, there are four equally scored domains of a hospital’s VBP score: safety, clinical care, cost reduction, and patient experience.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the work of Berwick and others, in 2013, the Centers for Medicare and Medicaid Services (CMS) initiated the hospital Value-Based Purchasing (VBP) program that altered hospital reimbursement from procedure-based to hospital performance data. This novel approach has challenged medical institutions to deliver high-quality care and reduce costs (Haley et al, 2016). As of 2018, there are four equally scored domains of a hospital’s VBP score: safety, clinical care, cost reduction, and patient experience.…”
Section: Introductionmentioning
confidence: 99%
“…16 One important component of this is the Patient Experience of Care domain, which constitutes 25% of provider TPS and is entirely dependent on subjective patient views of in-hospital care. 17 The patients' perspective of their experience of care is often measured by Press Ganey (PG) surveys, which encompass patient satisfaction elements as outlined by the Hospital Consumer Assessment of Healthcare Providers and Systems, with the benefit of allowing hospitals and physicians to compare their scores to others in the PG database. 18 PG surveys are currently utilized by more than 50% of hospitals in the United States.…”
mentioning
confidence: 99%
“…10,11 While market competition appears to be associated with the use of procedures and interventions, the relationship between market competition and quality of care has been inconsistent. While one report found that increased market competition was associated with decreased mortality for common medical conditions, 21 other studies have suggested that the influence of hospital competition on quality of care is minimal. 22,23…”
Section: Discussionmentioning
confidence: 99%